2019
DOI: 10.1061/(asce)cc.1943-5614.0000972
|View full text |Cite|
|
Sign up to set email alerts
|

Constitutive Model for Rubberized Concrete Passively Confined with FRP Laminates

Abstract: This article develops an analysis-oriented stress-strain model for rubberized concrete (RuC) passively confined with fiber reinforced polymer (FRP) composites. The model was calibrated using highly instrumented experiments on 38 cylinders with high rubber contents (60% replacement of the total aggregate volume) tested under uniaxial compression. Parameters investigated include cylinder size (100×200mm or 150×300mm; diameter×height), as well as amount (two, three, four or six layers) and type of external confin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…The results presented in this study, which has been lacking to date, regarding the fundamental cyclic properties of unconfined RuC materials, show that RuC can be used in expected plastic hinge zones of flexural members. On the other hand, for RRuC members with high axial loads such as column members, external confinement such as using steel tubes or FRP jackets [15,27,36,69,70], are required. However, for detailed numerical modelling of confined RuC, fundamental characteristics of unconfined RuC under cyclic loading are needed as have been quantified in this paper.…”
Section: Unloading Modulus and Residual Strainmentioning
confidence: 99%
See 2 more Smart Citations
“…The results presented in this study, which has been lacking to date, regarding the fundamental cyclic properties of unconfined RuC materials, show that RuC can be used in expected plastic hinge zones of flexural members. On the other hand, for RRuC members with high axial loads such as column members, external confinement such as using steel tubes or FRP jackets [15,27,36,69,70], are required. However, for detailed numerical modelling of confined RuC, fundamental characteristics of unconfined RuC under cyclic loading are needed as have been quantified in this paper.…”
Section: Unloading Modulus and Residual Strainmentioning
confidence: 99%
“…Importantly, most reported tests on the cyclic compressive response of RuC have been limited to rubber content levels below 30%, as a replacement of fine mineral aggregates, which corresponds to a relatively low rubber content of around 11% of the total mineral aggregates [26][27][28][29]. Limited studies, on the other hand, investigated the elastic mechanical properties of RuC with relatively high rubber content under cyclic compression or flexural loads [30][31][32][33][34][35][36][37]. However, the fundamental post-peak characteristics of unconfined RuC materials with relatively high rubber content under cyclic compression have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…External confinement, such as using fibre-reinforced polymer (FRP), provides a viable approach to recover some or all of the strength loss due to the presence of rubber [6]. FRP laminates were shown in previous studies to improve the capacity of RuC members under combined compression and bending loading and to provide high rotation capacity compared with RRuC members with internal stirrup confinement [7]. The capacity of FRP-confined RuC was between two to four times higher than unconfined RuC when the rubber content was 30% and 60%, respectively [8].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to FRP confined RuC, existing studies showed that FRP sheets have a significant influence on the structural behaviour of RuC members, including the load carrying capacity and the rotation capacity [8,9]. RuC members using FRP laminates can provide from two to four times higher strength compared with unconfined RuC counterparts [7,10].…”
Section: Introductionmentioning
confidence: 99%